PENGEMBANGAN APLIKASI KEAMANAN MOBILE UNTUK MENGAWASI JARINGAN RUMAH DARI JARAK JAUH - Winda Syukur, Winda Syukur; Fajrin, Alfannisa Annurullah (Computer Science and Industrial Engineering, 2024)
In the current era of globalization, the use of mobile devices has become an important part of daily life by providing easy internet access to various online service applications. Security is an important aspect to deal with increasing general crime in Indonesia, for this reason innovation is needed to develop a remote home security application to prevent theft. The solutionis to create a home monitoring tool that adopts CCTV cameras. Which uses ESP32-CAM as a microcontroller which can be monitored via the application, there is also a PIR Sensor to detect living objects. The output produced is a buzzer as an alarm sound warning and there is also a notification in the application.